Transfection Agent Induced Nanoparticle Cell Loading - Karin Montet-Abou; Xavier Montet; Ralph Weissleder; Lee Josephson (Molecular Imaging)
Loading cells with magnetic nanoparticles, and tracking their fate in vivo by high resolution MRI, is an attractive approach for enhancing the efficacy of cell-based therapies including those utilizing hematopoietic stem cells, neuroprogenitor cells, and T cells. The transfection agent (internalization agent) assisted loading with the Feridex IV ® nanoparticle is an attractive method of loading because of the low cost of materials, and possible low regulatory barriers for eventual clinical use. We therefore explored the interaction between Feridex IV ® and three internalization agents protamine (PRO), polylysine (PLL), and lipofectamine (LFA). Feridex reacted with internalization agents to form aggregates, except when either the internalization agent or Feridex was present in large excess. When Jurkat T cells were incubated with Feridex/LFA or Feridex/PRO mixtures, and washed by centrifugation, nanoparticle aggregates co-purified with cells. With C17.2 cells large iron oxide particles adhered to the cell surface. At 30 μg/mL Feridex and 3 μg/mL LFA, internalization was largely mediated by LFA and was largely cytoplasmic. However, we found that the conditions used to label cells with Feridex and transfection agents need to be carefully selected to avoid the problems of surface adsorption and nanoparticle precipitation.